1988
DOI: 10.1099/00221287-134-4-931
|View full text |Cite
|
Sign up to set email alerts
|

Further Analysis of Nitrogen Fixation (nif) Genes in Azotobacter chroococcum: Identification and Expression in Klebsiella pneumoniae of nifS, nifV, nifM and nifB Genes and Localization of nifE/N-, nifU-, nifA- and fix ABC-like Genes

Abstract: The results presented extend previous investigations on the genetics of nitrogen fixation in Azotobacter chroococcum and indicate that nif and$x-like DNA is located in at least five different regions of the genome. Region I contains functional copies of n i p , Vand M , as well as nzfH, D and K, all of which complemented mutants of Klebsiella pneumoniae. In addition, n$Eand/or nzfN-like and nzfLi-like DNA is located in this region. The organization of the nifcluster in region I closely resembles that of K. pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
8
0
4
Order By: Relevance
“…nifU, nifS, nifV, and nifM are clustered in a region of the A. chroococcum genome spanning about 7 kb (19). In our previous study, the approximate position of each gene was shown by (i) hybridization studies using various K. pneumoniae nifgene probes and (ii) the ability of plasmids pLC11, pSAR2a, and pSAR3a containing overlapping subfragments of this region (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…nifU, nifS, nifV, and nifM are clustered in a region of the A. chroococcum genome spanning about 7 kb (19). In our previous study, the approximate position of each gene was shown by (i) hybridization studies using various K. pneumoniae nifgene probes and (ii) the ability of plasmids pLC11, pSAR2a, and pSAR3a containing overlapping subfragments of this region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cultures were capped with Suba-Seals, and acetylene was added to 10o of the gas headspace. Acetylene reduction activities of K. pneumoniae strains were not determined as we have previously shown that strains complemented for growth on N2 display near-wild-type acetylene reduction levels, whereas strains not complemented for anaerobic growth show levels of acetylene reduction similar to the activity of the mutant strain alone (19). Protein in whole cells or crude extracts was measured by using the Folin-Ciocalteau reagent (42) with bovine serum albumin (fraction V; Sigma Chemical Co.) as a standard.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, thermolabile nifE null mutants were obtained. Yet, while nifE null mutants have been identified in various diazotrophic bacteria Evans et al, 1988), a thermolabile phenotype was not noted. NifE is purported to be important for biogenesis of the iron-molybdenum cofactor, itself required for dinitrogenase complex activity Imperial et al, 1987).…”
Section: Discussionmentioning
confidence: 99%